Grass species as raw material for pulp and paper [electronic publication] - Pahkala, Katri; Paavilainen, Leena; Mela, Timo (ca, 1999)
Paper has been made from grasses and other non-wood materials for over 1900 years. Wood is a relatively new papermaking fibre, only 100 years old. Today the commercial non-wood pulp production accounts for 6 % of the global pulp production. The main source for the raw material is plants of the Gramineae family. Research on non-wood material has concentrated on grasses like Miscanthus, Phalaris, Sorghum and cereals. The fibre properties of grass species studied are similar to those of hardwood. A case study on reed canary grass (Phalaris arundinacea L.) showed that the short-fibre fraction obtained from birch can be replaced with grass in fine paper.
Keywords: Ka; heinäkasvit; kuitukasvit; paperiteollisuus; grass species; paper making; pulp; pulp properties; reed canary grass; Phalaris arundinacea; non-wood; fibre